(untitled) (Research, Society and Development, 2022)
Neuroscientific studies, especially in the area of ​​cognition, have important contributions to the teaching-learning process, which makes it necessary to develop investigations that focus on the connections between neurological and pedagogical knowledge. Thus, this work presents an integrative bibliographical review of scientific articles that show the importance of neuroscience in the efficiency of educational processes. The data search was performed in Google Scholar, while the analysis followed the mapping guidelines proposed by Biembengut. A total of 12 articles were mapped, produced between 2003-2017, which demonstrate a historical course of neuroscience (discoveries, applications and limitations), as well as the various contributions of this area to the foundation of more efficient methodologies of teaching, as well as, the importance of the implementation of curricular components with the neural bases of learning, within teacher training courses. The research reveals, therefore, the potentiality of neuroscience as facilitator of the teaching-learning process, which is not effectively implemented, possibly due to the epistemological difficulties in attuning neurobiology and education.